Two Different Transplant Preconditioning Regimens Combined with Irradiation and Chemotherapy in the Treatment of Childhood Leukemia: Systematic Review and Meta-Analysis. (18th March 2022) - Wang, Xiangwen; Mu, Dan; Geng, Anyang; Zhao, Anqi; Song, Yiyuan
Abstract : Objective . To observe the therapeutic effect and the incidence of adverse reactions of total body irradiation plus cyclophosphamide (TBI/CY) and busulfan plus cyclophosphamide (BU/CY) in the treatment of pediatric hematopoietic stem cell transplantation. Methods . By searching the Cochrane Library, PubMed, Web of Knowledge, Embase, Chinese Biomedical Literature Database (CBM), and screening randomized controlled trials (RCTs), quality evaluation and data extraction were performed for the included literature, and meta-analysis was performed for RCTs included at using Review Manager 5.2 software. Results . A total of 10160 patients were enrolled in 15 RCTs, including 5211 patients in the TBI/CY group and 4949 patients in the BU/CY group. Meta-analysis showed that there was a statistical difference in transplant failure rate (OR = 1.56, 95% CI (1.23, 1.97), P = 0.0002, I 2 = 56%, Z = 3.69), transplant mortality (OR = 1.45, 95% CI (1.24, 1.68), P < 0.00001, I 2 = 76%, Z = 4.80), transplantation long-term disease-free survival rate (OR = 1.52, 95% CI (1.09, 2.12), P = 0.01, I 2 = 0%, Z = 2.50), and transplantation adverse reactions (OR = 1.28, 95% CI (1.08, 1.52), P = 0.004, I 2 = 0%, Z = 2.85). Conclusion . Meta-analysis showed that TBI/CY combined pretreatment regimen was more effective than BU/CY regimen alone in the treatment of pediatric hematologic transplantation, with a lower incidence of adverse reactions and significant long-term survival efficacy.